Governance at the Local Level in Melanesia – Absent the State - David Hegarty (Commonwealth Journal of Local Governance, 2009)
At independence the three Melanesian states of the Pacific Islands region – Papua New Guinea (1975), Solomon Islands (1978) and Vanuatu (1980) – opted for decentralised systems of government. In all cases a three-tier system of national, provincial and local government was introduced, although the specific arrangements and allocation of powers differed substantially. Since that time there has been a good deal of analysis about the policy processes of decentralisation itself and about the effectiveness (or otherwise) of national-level governance in these countries; but until recently little has been written about the lower levels.